Primary CNS Teratocarcinoma - Vitorovic, Danilo; Rosenblum, Jordan; Thomas, Chinnamma; Lee, John; Biller, Jose (Frontiers in Neurology, 2012)
Primary central nervous system (CNS) teratomas are rare tumors that consist of all three germ cell layers. We describe a young man with a primary malignant CNS teratocarcinoma presenting as leptomeningeal carcinomatosis. Diagnosis of primary CNS teratocarcinomas is challenging; relentless pursuit of the diagnosis must follow even if early ancillary studies are inconclusive.